Theory and Technology of Laser Imaging Based Target Detection - Hu, Yihua (Springer Singapore, 2018)
This book systematically introduces readers to laser imaging target detection principles and techniques. It covers the fundamentals of laser imaging and presents an extensive, up-to-date analysis of how to best use laser imaging to detect targets. This is followed by a comprehensive discussion of laser imaging target detection principles, laser imaging generation, and target detection methods. The book offers an invaluable resource for researchers, especially those who are engaged in the fields including target detection based on a laser imaging system, target detection and identification, remote sensing imaging and image processing. Additionally, it can be used as a reference book for advanced undergraduates and postgraduates of relevant majors.